Transient Oscillation Suppression Method of Modular Multilevel DC Transformer - Dan Lyu; Yichao Sun; Yufan Li; Jianfeng Zhao; Zhendong Ji; Dongye Li (IEEE Access, 2020)
The modular multilevel DC transformer (MMDCT) is more likely to suffer from transient oscillation, which is caused by insufficient damping of the equivalent RLC circuit with smaller arm resistance and submodule capacitance and may threaten the system stability. To tackle this issue, this paper conducts an in-depth analysis of the oscillation generating mechanism and thereby proposes a transient oscillation suppression method by incorporating an oscillation suppression angle (OSA) between the upper and lower arm switching voltages, with which the direction of the circulating current could be adjusted during this overlapped period. However, the open loop control of OSA shows indistinctive improvement of the damping ratio so that a damping compensator for regulating the circulating current is utilized. Furthermore, the compensating gain is optimally designed to achieve the critical damping state based on the small-signal model viewing OSA as an input variable. Besides, the outer capacitor voltage control loop and the power control loop are incorporated to provide the circulating current reference and to track the load power demand, respectively. Extensive simulation results from a realistically designed MMDCT model in PSIM validate the feasibility and effectiveness of the proposed transient oscillation suppression method.